Perlindungan Hukum Terhadap Upah Pekerja Kontrak Di Tinjau Dari Undang-Undang Ketenagakerjaan Indonesia Dan Hukum Islam - Lidia Febrianti; Rosyidi Hamzah; Febrina Andarina Zaharnika; Puti Mayang Seruni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Legal protection has a meaning as protection by using legal means or protection provided by law, aimed at the protection of certain interests, namely by making the interests that need to be protected into a legal right. to the wages of contract workers according to Law No. 13 of 2003 concerning Manpower and Islamic Law as well as similarities and differences. The results of this study indicate that the legal protection of the wages of contract workers between Law No. 13 of 2003 concerning Manpower and Islamic law is to show that legal protection of wages of contract workers has not guaranteed the welfare of contract workers and includes six things, namely: protection of workers / laborers women, protection of child workers/laborers, protection for persons with disabilities, protection of occupational health and safety, protection of labor social security and protection of wages. Meanwhile, according to Islamic law the protection provided is in the form of protection for the soul which is included in Islamic principles. As for the similarities and differences, namely that the two laws have the same goal of creating a sense of justice for workers and employers, and do not allow any arbitrariness against workers/labor. While the difference lies in the employment relationship, wages, welfare, functions and sanctions provided. Keywords: Protection, Wages, Workers, Contract Workers